Analisis Kepastian Hukum Pendaftaran Tanah Digital: Studi Komparatif Indonesia, Estonia dan Singapura - Andhika Purnama Seta (Jurnal Hukum Lex Generalis, 2026)
Digital land registration in Indonesia faces challenges regarding legal certainty due to vulnerabilities in data integrity and the reliability of electronic systems. This normative legal study analyses the legal certainty of digital land registration through a comparative study of Indonesia, Estonia and Singapore, employing legislative, comparative and conceptual approaches. The findings indicate that Indonesian regulations have not yet comprehensively addressed cybersecurity, whilst Estonia ensures legal certainty through data traceability based on the Keyless Signature Infrastructure (KSI) Blockchain, and Singapore strengthens legal accountability through Zero Trust Architecture controls. This study recommends a restructuring of Indonesian regulations based on Estonia’s data integrity principles and Singapore’s access controls to ensure legal certainty